2018
DOI: 10.1016/j.pmedr.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Sleep matters: The association of race, bedtime, outdoor time, and physical activity with preschoolers' sleep

Abstract: Sleep is necessary for optimal functioning. Little is known about the extent to which race and opportunities to be active influence sleep in preschool-aged children attending full-day child care. Participants (n = 359) in this cross-sectional study attended 30 randomly selected, childcare centers in Cincinnati, OH. Data collection occurred from November 2009 to January 2011. Hierarchical linear regression and generalized estimating equations tested for associations between nighttime sleep duration and race, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…Regarding the appropriate bedtime and sleep duration for children aged 5 years, the American Society of Sleep Medicine recommends sleep duration of 10-13 h for healthy preschool 3-5 years. 16 Parsons et al conducted a cross-sectional study involving 359 preschool children aged 3-5 years, and reported that about 65% went to bed before 21:00. and the average total sleep duration was 11.2 h. 17 In our study, average bedtime and sleep duration for 5-year-old children were 21:20 and 9.9 h, respectively. This indicated Japanese preschool children had a later bedtime and shorter sleep duration than children in Western countries.…”
Section: Discussionsupporting
confidence: 45%
“…Regarding the appropriate bedtime and sleep duration for children aged 5 years, the American Society of Sleep Medicine recommends sleep duration of 10-13 h for healthy preschool 3-5 years. 16 Parsons et al conducted a cross-sectional study involving 359 preschool children aged 3-5 years, and reported that about 65% went to bed before 21:00. and the average total sleep duration was 11.2 h. 17 In our study, average bedtime and sleep duration for 5-year-old children were 21:20 and 9.9 h, respectively. This indicated Japanese preschool children had a later bedtime and shorter sleep duration than children in Western countries.…”
Section: Discussionsupporting
confidence: 45%
“…43 Therefore, this study contributes the objective assessment of sleep duration to detect sociodemographic differences between groups. The difference in sleep duration may be a result of poor bedtime routines and sleep schedule, as it has been reported that African American preschoolers have less consistent bedtime routines 44 and later sleep onset 15 compared to white children, and these factors are associated with lower sleep duration. 15 Lower sleep duration in low-income children and families may be a result of bed sharing, additional environmental noise, longer parent work hours, and bedroom TV access, which occur more frequently in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have identified African American children may be more likely to nap at ECE centers, which may contribute to total sleep. 44 As screen-time and sleep may be related, the focus should remain on decreasing screen-time outside of the ECE center to increase nighttime sleep. The screentime data were self-reported and subject to social desirability bias, which may have influenced parents to report less screen-time than their child actually obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Several variables shown to be associated with sleep in children with and without epilepsy were measured using an investigator‐designed questionnaire and were included as covariates (Batista & Nunes, 2007; McDonald, Wardle, Llewellyn, van Jaarsveld, & Fisher, 2014; Parsons, Ollberding, Smith, & Copeland, 2018). These included the child's age, gender, daytime physical activity levels, seizure frequency, antiepileptic medication, developmental delay comorbidities, being the only child at home, and maternal employment.…”
Section: Methodsmentioning
confidence: 99%